Banana Bop! - Boynton, Sandra (New York, NY : Boynton Bookworks, 2025)
Banana Bop! is a book of few words-and most of them are "banana." But we challenge you to find a better word to repeat over and over again without smiling. First food, first word, first cascade of giggles: this irresistible board book is sure to make everyone go BANANAS!
new kids book 2025 spring.
Keywords: Bananas -- Juvenile fiction; Synonyms and anonyms; Board books